Correction of type IV (mixed level) total anomalous pulmonary venous drainage. Issue 2 (March 1972) - Neligan, M. C.; O'Malley, E.; Blake, S.
Abstract : Successful correction of type IV (mixed level) total anomalous pulmonary venous connexion (TAPVC) in a 5-year-old boy is reported. The actual pathway of the pulmonary venous drainage in this case has not previously been described in the literature.